Resolving the TorsinA Oligomerization Conundrum: The Glycan Hypothesis - Fercher, Christian; Zacchi, Lucía F. (Frontiers in Molecular Biosciences, 2020)
TorsinA is a AAA+ ATPase involved in the severe neurological disease Early Onset Torsion Dystonia. Despite the impressive progress in the field in the recent years, the structural organization and function of this intriguing molecule is still not clear. One outstanding difference between torsinA and other AAA+ ATPases is that torsinA is a glycoprotein. TorsinA N-linked glycans impact torsinA biogenesis and subcellular localization. Here, we propose that torsinA glycans also modulate torsinA oligomerization properties. We used structural modeling to test this idea, and show that N-linked glycans appear to restrict torsinA’s ability to form closed homohexameric ring assemblies, and instead promote an open hexameric conformation that allows torsinA interaction with key cofactors required for ATP hydrolysis. This mechanism would make torsinA a prime example of Nature’s sophisticated molecular glycoengineering.